إجراءات الدفع بعدم دستورية القوانين - تامه, الغالية; مقدود, مريم (University of Eloued جامعة الوادي, 2020)
أدرج المؤسس الدستوري الجزائري بموجب التعديل الدستوري لسنة 2016 في مجال الرقابة على دستورية القوانين, الرقابة اللاحقة عن طريق الدفع بعدم دستورية الأحكام التشريعية ضمن نص م 188 من القانون 16/01 المتضمن التعديل الدستوري, والتي تعد تأسيس دستوري لهذه الرقابة, التي تسمح للمتقاضي إثارة عدم دستورية الحكم التشريعي الذي طبق أو سيطبق على النزاع المطروح أمام الجهة القضائية التي تقوم بدورها بالبت في هذا الدفع إما برفضه أو قبوله, وإحالته على الجهات القضائية العليا ( المحكمة العليا أو مجلس الدولة ) التي تتكفل بعملية غربلة وتصفية طلبات الدفع في غضون المدة القانونية التي منحها إياها المشرع, وبذلك يتم تحديد مصير طلب الدفع في الاتصال بالمجلس الدستوري من عدمه. ويتولى المجلس الدستوري صلاحية البت في الدفع في أجل أربعة أشهر قابلة للتجديد مرة واحدة, وفي حالة ما إذا تم التصريح بعدم دستورية الحكم التشريعي محل الدفع بعدم الدستورية, فان ذلك يؤدي إلى إلغائه وفقدانه من النظام القانوني مما يجعل الجهة القضائية المعنية بالفصل في الدعوى الأصلية تواصل عملها بعد استبعاد ذلك الحكم التشريعي الملغى, ذلك أن القرار الذي اتخذه المجلس الدستوري يكتسي القوة الإلزامية في مواجهة الجميع باعتبار أن قرارات المجلس الدستوري تتمتع بالحجية المطلقة. The Algerian constitutional founder, according to the constitutional amendment of 2016 in the field of overseeing the constitutionality of laws, included subsequent oversight by arguing for the unconstitutionality of legislative provisions within the text of Article 188 of Law 01/16 containing the constitutional amendment, which is the constitutional establishment of this control, which allows litigants to raise the lack of The constitutionality of the legislative ruling that has been applied or will be applied to the dispute before the judicial authority which in turn decides on this defense either by rejecting it or accepting it, and referring it to the higher judicial authorities (the Supreme Court or the Council of State) that takes care of the process of screening and settling payment requests within the legal period granted by it By the legislator, and thus the fate of the payment request is determined by contacting the Constitutional Council or not. The Constitutional Council has the power to decide on the payment within a period of four months, which can be renewed once. Its action after excluding that repealed legislative provision, because the decision taken by the Constitutional Council acquires the mandatory force in the face of all, given that the decisions of the Constitutional Council enjoy absolute authenticity.
مذكرة ماستر